Amine decorated polystyrene nanobeads incorporating pi-conjugated OPV chromophore for picric acid sensing in water - Makkad, Sarabjot Kaur (RSC Advances, 2020)
A solution as well as solid state based sensor has been developed for selective detection of picric acid (PA) in water. Oligo (p-phenylenevinylene) (OPV) incorporated polystyrene nanobeads (PS-OPV-NH2) having an average size of 180 nm have been synthesized through miniemulsion polymerization. Amine (-NH2) functionalization was performed on the nanobead surface to enhance the efficiency of the sensor among a library of other nitro-organics and library of cations and anions.